Rd ch 5 McQ 11

Asked by ishmeet kaur Sidana | 21st Jul, 2013, 01:37: PM

Expert Answer:

We know that if p + q + r = 0, then p3 + q3 + r3 = 3pqr
Here, replace p = x - a, q = x - b, r = x - c
Then, 
p+q+r = 3x - (a+b+c) = 3x - 3x = 0      [Using the given condition]
Hence, 
(x - a)3 + (x - b)3 + (x - c)3 = 3(x-a)(x-b)(x-c)
(x - a)3 + (x - b)3 + (x - c)3 - 3(x-a)(x-b)(x-c) = 0

Answered by  | 21st Jul, 2013, 02:45: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.